Conservatism the fight for a tradition - Fawcett, Edmund (Princeton University Press, 2020)
"The sharp polarisation of left and right is commonly dwelt on as the big political handicap of our times. Angry divisions on the right itself get less attention. Conservatism fills that gap. Across Europe and the US, a liberal right is at war with an illiberal right. As the leading force in politics, it is vital to understand the roots of the right's struggle with itself, how it stands and how it is likely to come out. From its early 19th-century origins to now, conservatism never finally settled on how far to compromise with liberalism, democracy and the capitalist world out of which both grew. By the late 19th century, the mainstream right had come to terms with all three. Its reward was lasting success in the next century and beyond. On the political fringes and among ethical-cultural critics, a recalcitrant right, unreconciled to liberal democracy, never died. Resistance to liberal democracy is seen today in the hard right, a strange but potent alliance of hyper-liberal globalists and anti-liberal localists. Conservatism focuses on an exemplary core of France, Britain, Germany and the United States. It describes the parties, politicians and thinkers of the right, bringing out strengths and weaknesses in conservative thought. An appendix includes definitions of leading terms, a brief account of conservatism's philosophical origins and mini-lives of more than 200 conservatives. Historical and topical, neither celebration nor caricature, Conservatism is a unique, panoramic survey of the Western world's dominant political tradition"--